2021
DOI: 10.4103/psychiatry.indianjpsychiatry_532_20
|View full text |Cite
|
Sign up to set email alerts
|

Memory changes following adjuvant temporo-parietal repetitive transcranial magnetic stimulation in schizophrenia

Abstract: Objective: The use of repetitive transcranial magnetic stimulation (rTMS) in schizophrenia has shown improvement as well as deficits in memory. Though most studies had focused on dorsolateral prefrontal cortex only, but impact of rTMS on cognitive functions remain inconclusive. The need of the study is to assess the impact of rTMS on memory in schizophrenia. Materials and Methods: Forty right-handed male patients with schizophrenia were included by purposive sampling an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…In that review, twelve studies found evidence for a positive treatment effect of TMS on positive symptoms, whereas eighteen studies were inconclusive (Marzouk et al, 2020). We observed similar findings in our review, with half of relevant studies reporting reduced positive outcomes after rTMS (Gupta et al, 2021) (Ray et al, 2015) (Xie et al, 2021), and the remaining half reporting no improvement in positive symptoms (X. Li et al, 2020), (Lin et al, 2018), and (Tikka et al, 2015).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In that review, twelve studies found evidence for a positive treatment effect of TMS on positive symptoms, whereas eighteen studies were inconclusive (Marzouk et al, 2020). We observed similar findings in our review, with half of relevant studies reporting reduced positive outcomes after rTMS (Gupta et al, 2021) (Ray et al, 2015) (Xie et al, 2021), and the remaining half reporting no improvement in positive symptoms (X. Li et al, 2020), (Lin et al, 2018), and (Tikka et al, 2015).…”
Section: Discussionsupporting
confidence: 82%
“…Twelve studies used clinical outcome measures to assess the effect of rTMS in early psychosis patients (Francis et al, 2019) (Gupta et al, 2021) (Huang et al, 2022) (X. Li et al, 2020) (Lin et al, 2018) (Prikryl et al, 2014) (Ray et al, 2015) (Sverak et al, 2018) (Tikka et al, 2015) (Tikka et al, 2017) (Wang et al, 2022) (Xie et al, 2021).…”
Section: Rtms Is Associated With Clinical Improvements In Early Psych...mentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the different protocol used in our study may be the explanation that no significant effect on auditory hallucinations was observed. In addition, the lack of effect may be attributed to the relatively long causes of disease of the patients in this study; most of the patients here had been repeatedly hospitalized [ 65 , 66 ]. Furthermore, the short observation period of the current study may not have allowed us to observe an effect.…”
Section: Discussionmentioning
confidence: 99%